Scarless wound healing - a literature review - Ancuta Muntean; Ionica Stoica; Dan Mircea Enescu (Amaltea Medical Publishing House, 2019)
The healing of skin lesions, such as traumas or burns, can often result in severe scarring causing important disabilities. The study of fetal skin particularities brings into light its ability of healing wounds in a scarless manner, through regeneration. Understanding the cellular and molecular mechanisms of fetal scarless phenotype is of utmost importance as it can result in new therapeutic targets that could have the potential to reduce scarring in postnatal wounds. The aim of this review is to summarize the unique features of fetal wound healing process that may facilitate a scarless wound repair.